Risk behaviors, prevalence of HIV and hepatitis C virus infection and population size of current injection drug users in a China-Myanmar border city: results from a Respondent-Driven Sampling Survey in 2012. - Lei Li (Public Library of Science (PLoS), 2014)
Background Injection drug use has been the major cause of HIV/AIDS in China in the past two decades. We measured the prevalences of HIV and hepatitis C virus (HCV) prevalence and their associated risk factors among current injection drug users (IDUs) in Ruili city, a border region connecting China with Myanmar that has been undergoing serious drug use and HIV spread problems. An estimate of the number of current IDUs is also presented. Methods In 2012, Chinese IDUs who had injected within the past six months and aged ≥ 18 years were recruited using a respondent-driven sampling (RDS) technique. Participants underwent interviews and serological testing for HIV, HBV, HCV and syphilis. Logistic regression indentified factors associated with HIV and HCV infections. Multiplier method was used to obtain an estimate of the size of the current IDU population via combining available service data and findings from our survey. Results Among 370 IDUs recruited, the prevalence of HIV and HCV was 18.3% and 41.5%, respectively. 27.1% of participants had shared a needle/syringe in their lifetime. Consistent condom use rates were low among both regular (6.8%) and non-regular (30.4%) partners. Factors independently associated with being HIV positive included HCV infection, having a longer history of injection drug use and experience of needle/syringe sharing. Participants with HCV infection were more likely to be HIV positive, have injected more types of drugs, have shared other injection equipments and have unprotected sex with regular sex partners. The estimated number of current IDUs in Ruili city was 2,714 (95% CI: 1,617-5,846). Conclusions IDUs may continue to be a critical subpopulation for transmission of HIV and other infections in this region because of the increasing population and persistent high risk of injection and sexual behaviours. Developing innovative strategies that can improve accessibility of current harm reduction services and incorporate more comprehensive contents is urgently needed.